MAKNA “NASIONALISME NEGARA- BANGSA” MELALUI TEKS MEDIA - Somo Arifianto (Jurnal Studi Komunikasi dan Media, 2013)
ABSTRACTNationalism has a strategic role in maintaining identity of nation-state. Although it is disputable. This article describes and analyses it from some perspectives. The results are: (a) From economic perspective, it emerges a pragmatic need to achieve dominan economic growth. It’s expected to contribute to public welfare, economic stability for nationalism, nation-state; (b). From economic, social politic perspective, globalization and local community strengthenment which is caracterized by regional authonomy. If there is mismanagement, it wil be an obstruction for nationalism; (c). From cultural perspective, there is an indication that culture tends to unravel nationalism, nation-state. Therefore, “glocalisation” of culture in local community should not be viewed as counternationalism againts nation-state, on the contrary, it strengthens nationalism, in the context of nation-state. Media contents is able to frame and articulate representation & nationalism concept.  Nation-state is not only in the cognitif level, but also in the level nationalism ideology, nation-state. Hence, nationalism spirit of nation-state must be bolstered, although only by construction on media text.  Keywords:  Media Text; Strengthenment of Nation-state nationalism ideology. ABSTRAKNasionalisme memiliki peran strategis untuk mempertahankan identitas Negara-bangsa, meski masih menjadi persoalan diskursif. Tulisan artikel ini mencoba untuk mendiskripsikan dan menganalisis dari berbagai perspektif. Hasilnya adalah: (a). Dari perspektif ekonomi,  muncul kebutuhan pragmatis untuk mencapai pertumbuhan ekonomi dominan, diartikulasikan dapat mendorong tercapainya kesejahteraan masyarakat untuk menciptakan stabilitas ekonomi, demi nasionalisme, negara-bangsa; (b). Dari perspektif sosial politik, proses globalisasi dan penguatan komunitas lokal yang bercirikan otonomi daerah jika salah implementasinya bisa menjadi ancaman nasionalisme; (c). Dari perspektif budaya muncul gejala bahwa kebudayaan cenderung melepaskan keterikatannya pada nasionalisme, negara-bangsa. Proses “glokalisasi” budaya di komunitas masyarakat lokal hendaknya tidak dilihat sebagai kontra “nasionalisme negara-bangsa”, tetapi justru menjadi penguatan nasionalisme dalam kontek negara-bangsa. Pada akhirnya, teks media mampu membingkai dan mengartikulasikan representasi dan konsep nasionalisme, negara-bangsa bukan sekedar pada tataran kognitif, tetapi juga pada ideologi nasionalisme, negara-bangsa. Pada titik itulah semangat nasionalisme negara-bangsa dapat dibangkitkan, meski hanya melalui konstruksi teks media. Kata-kata Kunci: teks media, penguatan ideologi nasionalisme negara-bangsa